Exploring the Altruistic-Integrated Samawa Local Wisdom in Sumbawa’s Scout Movements as A Model of Character Education - AR, Rusdianto; Rasyad, Ach; Dayanti, Umi; Zulkarnain, Zulkarnain (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to explore the the altruistic-integrated Samawa local wisdom in Sumbawa’s Scout Movements as a model of character education. This research used a qualitative approach with a phenomenological method. The data was collected through interviews, observations, and documentary studies. The data analysis technique used the Miles and Huberman model with the following stages: data reduction, data presentation, and conclusion drawing/verification. The findings indicate that the Samawa cultural values are inextricably linked to scout education. Samawa’s indigenous cultural values, which include kerik salamat (abundance of gratitude and faith), to and ila (knowledge and shame), concern for the nation and homeland, mutual values (togetherness), self-care, pamendi and penyadu (obedience to a code of conduct) are closely related to five altruistic characteristics, namely empathy, belief in a just world, social responsibility, internal locus of control, and low egocentrism. These findings indicate that Samawa’s indigenous wisdom, when combined with altruistic components, plays a significant role in learning, both in formal and non-formal education settings. Based on these findings, it can be concluded that various scouting activities, which were accompanied by the cultivation of the noble values of the Samawa culture, were effective in increasing students’knowledge about scouting. The results of the research analysis can serve as a guide for stakeholders interested in enhancing students’ character qualities in Indonesia.